Physical therapy care to community-dwelling individuals with stroke in primary care setting in Brazil: a cross-sectional study - Jordana de Paula Magalhães; Tamires Mariana de Freitas Vieira Dutra; Érika de Freitas Araújo; Luci Fuscaldi Teixeira-Salmela; Christina Danielli Coelho de Morais Faria (Universidade de São Paulo, 2024)
ABSTRACT After hospital discharge, it is recommended that post-stroke individuals receive follow-up by a physical therapist throughout all the stages of recovery. Despite clinical recommendations, few studies have investigated physical therapy care to community-dwelling individuals with stroke. This study aimed to describe physical therapy care to community-dwelling individuals with stroke in primary care setting and identify clinical-functional and sociodemographic characteristics that determined physical therapy assistance. This is an exploratory cross-sectional study. Community-dwelling individuals with stroke who were assisted by the primary healthcare team from an important Brazilian metropolis were included. Their medical records were analyzed to identify the care provided by physical therapists. Individuals who received and did not receive physical therapy care were compared (α=0.05). Out of the 100 included individuals, 55% received assistance from the multidisciplinary primary healthcare team and 44% from physical therapists. Physical therapy approaches consisted mainly of general orientations (89%) and assessments (75%). Only 45% of the individuals who received physical therapy care were followed-up, and those who received this type of care had significantly more stroke events and higher levels of disability (p<0.001). It was observed that many individuals with various levels of disabilities have not received physical therapist assistance. Moreover, follow-up care and referrals were not frequent physical therapy approaches. Therefore, physical therapy care in primary care needs to be expanded to ensure that all individuals with some level of disability receive treatment. Moreover, it is necessary to increase the number of individuals receiving follow-up and encourage multidisciplinary work between physical therapists and other primary healthcare professionals.